Histoire de la sexualite - Foucault, Michel (Bibliothèque des histoires, 2018)
"Nommé au Collège de France, Michel Foucault a entrepris, durant la fin des années soixante-dix, un cycle de cours consacré à la place de la sexualité dans la culture occidentale : l'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi). Il y prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir, mais en concentrant ses analyses sur la constellation de phénomènes que nous désignons par le «sexe» et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une «répression» de la sexualité afin de la «libérer», mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une «science de la sexualité», laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence. Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de «libération sexuelle», l'attitude de censure et celle d'affranchissement se rencontrant finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur."Dans ce deuxième volume, Foucault poursuit son enquête historique sur les sources de notre sexualité occidentale. Il a dû infléchir son projet initial pour s'intéresser aux sources antiques, grecques et surtout romaines. La recherche se développe selon tous les aspects concernés par la sexualité et prend, ainsi, les dimensions d'une anthropologie générale du plaisir. Foucault ne néglige pas non plus l'économie de la sexualité et son inscription dans un cadre social et juridique, et il étudie le statut du mariage, ainsi que l'organisation des foyers. Enfin, l'ouvrage se conclut sur un traité d'érotique et une réflexion sur ce que serait l'amour véritable."-- Site de l'éditeur."Le troisième volume de l'histoire de la sexualité est consacré à la formation de l'individu telle qu'elle a été développée à travers des textes souvent peu analysés - Artémidore, Galien, le Pseudo-Lucien -, mais déterminants dans la mise en place d'une finalité générale de la culture qui culmine dans l'émergence d'une personnalité singulière, capable de faire le meilleur usage de son corps et de son esprit harmonieusement éduqué pour le rendre à même d'assumer les fonctions politiques auxquelles il est d'emblée destiné. Le souci de soi n'est pas égoïsme étroit, mais recherche de la vie selon un ordre qui assure la pérennité de la Cité, et que l'on cherche à déduire de la nature telle qu'on en comprend les lois. Foucault se révèle ainsi en quête de rétablir certains liens, rompus par la modernité, avec une tradition antique classique qu'il nous fait redécouvrir."-- Site de l'éditeur."Les aveux de la chair, qui paraît aujourd'hui comme le quatrième et dernier volume de L'histoire de la sexualité, est en réalité le premier auquel Michel Foucault s'était consacré après La volonté de savoir (1976) qui constituait l'introduction générale de l'entreprise. Il s'attachait aux règles et doctrines du christianisme élaborées du IIe au IVe siècles par les Pères de l'Église. Au cours de son travail, Michel Foucault s'était persuadé que l'essentiel de ces règles et doctrines était un héritage remanié des disciplines de soi élaborées par les philosophes grecs et latins de l'Antiquité classique et tardive. C'est à leur analyse qu'il s'est courageusement appliqué, pour aboutir en 1984 à la publication simultanée de L'usage des plaisirs et du Souci de soi. L'ouvrage est donc un premier jet auquel Foucault comptait se remettre au moment de sa mort. La réunion des quatre volumes de Dits et Écrits (1954-1988) publiés en 1994, puis celle des treize volumes des Cours au Collège de France en ont retardé l'édition et la mise au point dont s'est chargé Frédéric Gros, l'éditeur des œuvres de Michel Foucault dans la Bibliothèque de la Pléiade. Tel quel, cet ouvrage constitue un état très élaboré de la pensée de l'auteur et peut-être le cœur même de l'entreprise, la partie à laquelle il attachait assez d'importance pour se lancer dans l'aventure."-- Site de l'éditeur.
Keywords: approches et analyses; cours; discipline; histoire; histoire et politique; lit4700; philosophie; premier cycle; queer; sciences humaines; sexualité; soc2014; thématiques

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Feminism is queer: the intimate connection between queer and feminist theory - Marinucci, Mimi (Zed Books, 2016)
Feminism is Queer is an introduction to the intimately related disciplines of gender and queer theory. While guiding the reader through complex theory, the author develops the original position of "queer feminism, " which presents queer theory as continuous with feminist theory. While there have been significant conceptual tensions between second wave feminism and traditional lesbian and gay studies, queer theory offers a paradigm for understanding gender, sex, and sexuality that avoids the conflict in order to develop solidarity among those interested in feminist theory and those interested in lesbian and gay rights. This accessible and comprehensive textbook carefully explains nuanced theoretical terminology and includes extensive suggested further reading to provide the reader with a full andthorough understanding of both disciplines.--Publisher information.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; militance; philosophie; premier cycle; queer; sciences humaines; soc2014; thématiques

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Esthétique(s) "queer" dans la littérature et les arts: sexualités et politiques du trouble - Plana, Muriel; Sounac, Frédéric (1969- ...).; Beauchamp, Hélène (1977- ...).; Bret-Vitoz, Renaud (1972- ...).; Garnier, Emmanuelle (1964- ...).; Plana, Muriel; Sounac, Frédéric; Beauchamp, Hélène; Bret-Vitoz, Renaud; Garnier, Emmanuelle (Écritures, 1630-0858, 2015)
"En important dans le champ de l'esthétique le concept de "queer" issu des pensées du genre et en s'inscrivant dans une perspective interdisciplinaire, tant du point de vue des arts étudiés (littérature, arts de la scène, du corps et de l'image) et des méthodes adoptées (approches littéraires, sociocritique, philosophie, "gender studies", "women studies", "queer studies" ...), cet ouvrage collectif s'attache à ce qui, dans des productions artistiques contemporaines mais aussi plus anciennes, tend à jeter le trouble, politiquement et formellement, dans la représentation des identités sexuelles, des sexualités et de l'érotisme. Le livre fait par conséquent le pari que le travail des écrivains et des artistes autour du travestissement et des homosexualités ou encore leur intérêt pour la représentation de phénomènes comme le transgenre ou le "transsexualisme" leur permettent de penser ou de repenser, entre transgression et subversion, les concepts de "queer" et d'"esthétique", ainsi que de transformer radicalement nos représentations et notre façon d'envisager l'histoire des arts, des idées et des sociétés." [Source : 4e de couv.].
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; esthétique; har4600; histoire de l'art; identités LGBTQIA2+; philosophie; premier cycle; queer; sciences humaines; thématiques; théorie de l'art

The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Défaire le genre - Butler, Judith (Éditions Amsterdam, 2012)
"Faire" son genre implique parfois de défaire les normes dominantes de l'existence sociale. La politique de subversion qu'esquisse Judith Butler ouvre moins la perspective d'une abolition du genre que celle d'un monde dans lequel le genre serait "défait", dans lequel les normes du genre joueraient autrement, tout autrement. ... Ce livre, qui constitue un retour critique sur les analyses développées par l'auteure dans "Trouble dans le genre", s'inscrit dans une démarche indissociablement théorique et pratique : il s'agit, en s'appuyant sur les théories féministe et queer, de faire la genèse de la production du genre et de travailler à défaire l'emprise des formes de normalisation qui rendent certaines vies invivables, ou difficilement vivables, en les excluant du domaine du possible et du pensable. ... Judith Butler s'attache notamment dans les présents essais - ancrés dans l'actualité des politiques et des savoirs du genre, de la sexualité et de la parenté -, à mettre en évidence les contradictions auxquelles sont confrontés ceux et celles qui s'efforcent de penser et transformer le genre."
Keywords: amériques; approches et analyses; com5170; cours; discipline; fem1000; genre; har4600; identités LGBTQIA2+; lit4700; philosophie; pol4022; premier cycle; queer; régions géographiques; sciences humaines; sexe; sexualité; soc2014; thématiques; états-unis

Régulation du genre - Butler, Judith (Défaire le genre, 2012)
Keywords: amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; philosophie; premier cycle; queer; régions géographiques; sciences humaines; sexe; sexualité; thématiques; états-unis

Réflexions autour de la notion d’homophobie: succès politique, malaises conceptuels et application empirique - Chamberland, Line; Lebreton, Christelle (Nouvelles Questions Féministes, 2012)
Après en avoir retracé rapidement la genèse, cet article rapporte les principales critiques adressées au concept d’homophobie, notamment son réductionnisme qui tend vers des explications de nature psychologique ainsi que l’éviction de la hiérarchie des sexes/genres. Nous discutons ensuite deux pistes théoriques permettant de contourner les limites précédemment identifiées. La première examine le potentiel de l’approche intersectionnelle. La seconde voie invite à une redéfinition du concept d’homophobie, lui reconnaissant une portée exclusivement descriptive, et non plus en tant que concept explicatif, justifiant ainsi sa subordination au concept d’hétérosexisme qui offre une perspective systémique. Nous examinons ces concepts en fonction de leur capacité à rendre compte de l’oppression des lesbiennes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

La notion d'homophobie, ses usages et son rapport au féminisme - Perrin C.; Roca I Escoda M.; Parini L. (Nouvelles Questions Feministes, 2012)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; homosexualité; hétérosexisme; identités LGBTQIA2+; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; sciences humaines; sexualité; systèmes d'oppressions; thématiques

“I would rather be a cyborg than a goddess” Becoming-intersectional in assemblage theory - Puar, Jasbir K. (philoSOPHIA, 2012)
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; intersectionnalité; philosophie; queer; ressource en ligne; sciences humaines

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Les relations d'amitié - Martin, Hélène; Hertz, Ellen; Messant, Françoise; Delphy, Christine; Füger, Helene; Sala, Alice (Nouvelles Questions Féministes, 2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; amitié; approches et analyses; cours; discipline; europe; hétérosexisme; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

The promise of happiness - Ahmed, Sara (Duke University Press, 2010)
« The Promise of Happiness is a provocative cultural critique of the imperative to be happy. It asks what follows when we make our desires and even our own happiness conditional on the happiness of others: 'I just want you to be happy', 'I'm happy if you're happy'. Combining philosophy and feminist cultural studies, Sara Ahmed reveals the affective and moral work performed by the 'happiness duty', the expectation that we will be made happy by taking part in that which is deemed good, and that by being happy ourselves, we will make others happy. Ahmed maintains that happiness is a promise that directs us toward certain life choices and away from others. Happiness is promised to those willing to live their lives in the right way. Ahmed draws on the intellectual history of happiness, from classical accounts of ethics as the good life, through seventeenth-century writings on affect and the passions, eighteenth-century debates on virtue and education, and nineteenth-century utilitarianism. She engages with feminist, antiracist, and queer critics who have shown how happiness is used to justify social oppression, and how challenging oppression sometimes causes unhappiness. Reading novels and films including "Mrs. Dalloway", "The Well of Loneliness", "Bend It Like Beckham", and Children of Men, Ahmed considers the plight of the figures who are challenged by, and themselves challenge, the attribution of happiness to particular objects or social ideals: the feminist killjoy, the unhappy queer, the angry black woman, and the melancholic migrant. Through her readings, she raises critical questions about the moral order imposed by the injunction to be happy. »--Quatrième de couverture.
Keywords: approches et analyses; bonheur; care; discipline; inégalités; philosophie; queer; racisme; représentations; sciences humaines; sexisme; systèmes d'oppressions; thématiques; études culturelles

« La sexualité des femmes: le plaisir contraint », Nouvelles Questions Féministes, n° 3, 2010 - Guichard-Claudic, Yvonne; Andro, Armelle; Bachman, Laurence; Bajos, Nathalie; Hamel, Christelle (Nouvelles Questions Féministes, 2010)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; corps; corps féminin; cours; discipline; discours dominant; europe; france; hétérosexisme; intersectionnalité; phi2030; philosophie; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sexualité des femmes*; systèmes d'oppressions; thématiques